Penguatkuasaan nilai moral melalui undang-undang di Malaysia: Analisis ke atas kesalahan jenayah syariah (Wilayah-wilayah Persekutuan) 1997 dan Akta Prosedur Jenayah Syariah (Wilayah-Wilayah Persekutuan) 1997 - Ahmad ‘Azam Mohd Shariff, (Fakulti Undang - Undang, 2007)
The incident on the of January 2005 which saw JAWI officials raiding an entertainment center in Jalan Ampang Kuala Lumpur and arresting muslims for the offence against morality had attracted a lot of criticisms on its enforcement. Despite that, this writing upholds justification for legal enforcement of moral values through the Syariah Criminal Offence (Federal Territories) Act 1997 and the Syariah Criminal Procedures (Federal Territories) Act 1997. This writing then attempts to answer all criticisms relating to the incident on the night of of January 2005. Simultaneously, a few weaknesses relating to the current syariah legal provisions and enforcement are also identified. Last but not least, a few positive suggestions are hereby given in the effort of improving future enforcement of moral values in the society, while preserving the holiness of Islam as the official religion of this country